Improving students' ability to write narrative texts using pictures - Eliyawati Eliyawati (Universitas Muhammadiyah Ponorogo, 2020)
This study is aimed in improving students' writing ability by using pictures in narrative text for Grade XI- IPS 5 SMA N 1 Cigugur Kuningan, the survey used of t-test data of experimental and control groups on pre-test and the shows that tactic is lower that ttab (0, 07 ˂ 1, 6759) that is no significant difference of pre-test mean of both groups. The result of there are given a different treatment, and it means that there is a considerable difference in the post-test way of both groups, which is the post-test mean of the experimental group is significantly higher. The result t-test of a hypothesis test in the experimental group, whit is tactic ˃ tab or 9, 72 ˃ 1, 7081 so the alternative hypothesis (Ha) the researcher found that the students gave positive responses on the use of the picture on student narrative writing skill. The results of the questionnaire analysis were only offered to the experimental group, which for the affective aspect was 370 or with the